Chromosomal aberrations and CNVs in twin fetuses with cardiovascular anomalies: Comparison between monochorionic diamniotic and dichorionic diamniotic twins. (25th March 2018) - Zhang, Yi; Huang, Linhuan; Huang, Xuan; He, Zhiming; Lin, Shaobin; Wang, Ye; Li, Lin; Luo, Yanmin; Fang, Qun
Abstract: Objective: To investigate the types of cardiovascular anomalies and the results of invasive prenatal diagnosis in twin fetuses. Methods: A total of 298 fetuses in 149 twin pairs were enrolled, in which 1 or 2 fetuses of a twin pair had cardiovascular anomalies. Prenatal diagnosis was performed on 290 fetuses of 149 twin pairs, including 150 monochorionic diamniotic (MCDA) fetuses (79 pairs) and 140 dichorionic diamniotic (DCDA) fetuses (70 pairs). G‐Banding karyotyping and/or chromosomal microarray analysis were performed. The types of cardiovascular anomalies and the results of prenatal diagnosis were analyzed. Results: Fifty percent (79/158) fetuses in MCDA group and 52.1% (73/140) fetuses in DCDA group were diagnosed with cardiovascular anomalies by ultrasound. Primary cardiac structural defects such as septal defects and tetralogy of Fallot were more common in DCDA group than in MCDA group, while acardiac anomaly was the most common in MCDA group. Chromosomal aberrations were identified in 7.7% fetuses (11/142) of MCDA group and in 18.3% fetuses (22/120) of DCDA group by G‐banding karyotyping. Except benign copy number variations (CNVs), 37 CNVs (pathogenic, likely pathogenic, and variant of uncertain significance) and chromosomal aberrations were detected in 21.3% (32/150) fetuses of MCDA group and 47 CNVs (pathogenic, likely pathogenic, and variant of uncertain significance) and chromosomal aberrations were detected in 32.1% (45/140) fetuses of DCDA group by chromosomal microarray analysis. Conclusions: Most of cardiovascular anomalies were identified in one fetus of a twin pair no matter in MCDA or DCDA twin. Primary cardiac structural defects were more common in DCDA group. Monozygotic twins may have discordant phenotypes, karyotypes, and CNVs between 2 fetuses of each pair. Abstract : What's already known about this topic? Some chromosomal aberrations and copy number variations (CNVs) in twin fetuses with congenital heart disease could be detected by karyotyping and chromosomal microarray analysis. What does this study add? We compare the differences of cardiovascular anomalies' distribution between monochorionic diamniotic (MCDA) and dichorionic diamniotic (DCDA) twins. We also analyze the detailed results of invasive prenatal diagnosis in twin fetuses with cardiovascular anomalies in MCDA and DCDA twins. We further highlight the discordant phenotypes, karyotypes, and CNVs between 2 fetuses of monozygotic twin pairs.